Plastid peptidoglycan - Takano, Hiroyoshi; Takechi, Katsuaki (Biochimica et biophysica acta, 2010)
It is now widely accepted that an endosymbiotic cyanobacterium evolved into the plastid of the primary photosynthetic eukaryotes: glaucocystophytes, red algae, and green plants. It has been thought that during the evolution of plants, the peptidoglycan wall (or murein) was lost from the endosymbiont immediately after the branching off of the glaucocystophytes, which have peptidoglycan-armed plastids termed cyanelles. However, we found that the moss Physcomitrella patens has all of the genes for peptidoglycan biosynthesis with the exception of one racemase. The aim of the present review is to summarize recent findings on plastid peptidoglycan and to present a hypothesis for the evolution of plastids containing peptidoglycan. Gene knockout experiments for the Mur( ein) genes, including MurE in P. patens, showed that the peptidoglycan synthesis pathway is related to plastid division, although no structure can be detected between the inner and outer envelopes of the chloroplasts by electron microscopy. On the other hand, MurE in Arabidopsis thaliana has a function in plastid gene expression and not in division. Based on data regarding plant genomes and antibiotic treatment experiments of plastid division, we propose that the loss of peptidoglycan occurred independently at least three times during plant evolution: from the lineage of red algae, from the chlorophytes, and during land plant evolution.